2006
DOI: 10.1111/j.1365-2621.2006.tb08921.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Factors on Firmness and Color Evolution During the Storage of Persimmon cv. ‘Rojo Brillante’

Abstract: ‘Rojo Brillante’ persimmons were harvested in 2 different dates, early and late, and then submitted to 1‐methylcyclopropene (1‐MCP) treatment (500 nL/L) before stored at 1 or 15 °C up to 50 or 30 d, respectively. The influence of harvest date, 1‐MCP treatment, orchard, storage time, and temperature on firmness loss and color evolution during storage of ‘Rojo Brillante’ persimmon was studied. Statistical models that allowed the prediction of these 2 quality parameters during the storage, as well as the modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“…'Rojo Brillante' shows the greatest sensitivity to low temperatures during early stages of maturity (Salvador et al, 2005(Salvador et al, , 2006. For this reason, the effect observed in the present work is especially interesting, because HWT could become a possible alternative to prolonging low-temperature fruit storage.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…'Rojo Brillante' shows the greatest sensitivity to low temperatures during early stages of maturity (Salvador et al, 2005(Salvador et al, , 2006. For this reason, the effect observed in the present work is especially interesting, because HWT could become a possible alternative to prolonging low-temperature fruit storage.…”
Section: Discussionmentioning
confidence: 69%
“…Previous reports for this cultivar showed that these fruit are sensitive at temperatures below 11°C; the main chilling injury (CI) symptom is softening when fruit are transferred to higher temperature (Arnal and Del Rio, 2004;Salvador et al, 2004). Like other fruit, 'Rojo Brillante' persimmon showed higher sensitivity to low temperatures when they were picked at early maturity stages (Salvador et al, 2005(Salvador et al, , 2006.…”
mentioning
confidence: 93%
“…Therefore, in general, the less coloured the fruit, the higher must be the storage temperature and the shorter the storage time (Testoni 2002). Salvador et al (2006) reported early-harvested fruit showed more sensitivity to low temperature, with 18C eliciting the highest incidence of CI symptoms compared with late-harvested fruit. Consistent with this understanding, cultivars tested in this study were harvested at the full orange colour stage and, therefore, did not exhibit CI.…”
Section: Discussionmentioning
confidence: 99%
“…This is not unanticipated in view of the obligatory requirement of ethylene for the initiation and completion of normal ripening in climacteric fruit (Klee, 2004;Lelièvre et al, 1997). Notable responses of climacteric fruits include altered ethylene production and respiration (Ergun et al, 2005b;Golding et al, 1998;Ortiz et al, 2006;Zhang et al, 2006), delayed or suppressed softening (Adkins et al, 2005;Ergun et al, 2005b;Liguori et al, 2004;Menniti et al, 2006;Salvador et al, 2006;Sane et al, 2005;Toivonen and Lu, 2005;Watkins and Nock, 2005), and altered or delayed volatile emissions (Defilippi et al, 2005;El-Sharkawy et al, 2005;Li et al, 2006;Mattheis et al, 2005;Pre-Aymard et al, 2005;Rizzolo et al, 2005). Evident from these and other studies is that there are no cases in which climacteric fruits have not responded significantly and dramatically to 1-MCP.…”
mentioning
confidence: 99%